2021
DOI: 10.21037/tcr-21-1937
|View full text |Cite
|
Sign up to set email alerts
|

Dexmetomidine promotes the activity of breast cancer cells through miR-199a/HIF-1α axis

Abstract: Background Breast cancer, as one of the most common malignant tumors in women, is still a great threat to women all over the world. Dexmetomidine (DMED) is a highly selective α2-adrenergic receptor agonist, which has attracted much attention in recent years. This study aimed to clarify the potential mechanism of DMED in regulating the activity of breast cancer cells. Methods Breast cancer cell lines MCF-7 and MDA-MB-231 were treated with DMED. The levels of miR-199a and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Based on in vitro and xenotransplant in vivo assays, Xia et al reported that dexmedetomidine could increase the proliferation, migration, and invasion of breast cancer cells via activation of α2B-adrenoceptor / ERK signaling[45]. Subsequent studies have corroborated this finding and proposed explanatory mechanisms[46][47][48][49], while none have shown a finding of sufficient significance to discourage use of the anesthetic.…”
mentioning
confidence: 99%
“…Based on in vitro and xenotransplant in vivo assays, Xia et al reported that dexmedetomidine could increase the proliferation, migration, and invasion of breast cancer cells via activation of α2B-adrenoceptor / ERK signaling[45]. Subsequent studies have corroborated this finding and proposed explanatory mechanisms[46][47][48][49], while none have shown a finding of sufficient significance to discourage use of the anesthetic.…”
mentioning
confidence: 99%
“…In colon cancer, upregulation of MYO1B promoted tumor metastasis by mediating the RhoA/ROCK/FAK signaling pathway, resulting in poor prognosis in patients 44 . Besides, increased expression of MYO1B could also be detected in cervical cancer tissues, 45 which was correlated with high proliferation and invasive ability of cervical cancer cells and unfavorable outcomes 46 . Taken together, overexpression of MYO1B may promote proliferation, metastasis, and invasion in a variety of cancers.…”
Section: Discussionmentioning
confidence: 96%
“…MYO1B, Myosin 1b. proliferation and invasive ability of cervical cancer cells and unfavorable outcomes 46. Taken together, overexpression of MYO1B may promote proliferation, metastasis, and invasion in a variety of cancers.…”
mentioning
confidence: 99%
“…Dexmedetomidine is a centrally acting a2 adrenoreceptor agonist used perioperatively for sedative, analgesic and sympatholytic properties. Although limited clinical studies exist, recent animal model data points towards dexmedetomidine's potential role in promoting cancer recurrence and metastasis, especially after breast cancer surgery [66], possibly related to the presence of a2 adrenoreceptors in breast cancer tissue [67]. Sparse evidence also suggests dexmedetomidine may reduce the degree of immunosuppression during cancer surgery.…”
Section: Does Dexmedetomidine Affect Cancer Outcomes?mentioning
confidence: 99%